Mechanisms of safranin O interaction with 1:1 layered clay minerals. Issue 12 (13th August 2021) - Hebert, Jessica; Wang, Lijuan; Wang, Xisen; Baker, Jessica; Rivera, Nick; Troedel, Michael; Li, Zhaohui
ABSTRACT: Using Earth materials for the removal of environmental contaminants attracted great attention. In this study, the mechanism of safranin O (SO) removal by 1:1 layered clay minerals was investigated. The specific surface area and cation exchange capacity of the minerals played a key role, while solution pH and ionic strength had less influences on SO removal. The sorption of counterion Cl – on halloysite nano clay (HNC) at high loading levels resulted in bilayer SO formation on HNC surfaces. Lack of Cl – sorption on kaolinite (KAO) suggested monolayer SO formation on KAO surfaces. These speculations were confirmed by molecular dynamic simulation.